Taxifolin ameliorate high-fat-diet feeding plus acute ethanol binge-induced steatohepatitis through inhibiting inflammatory caspase-1-dependent pyroptosis. Issue 1 (16th December 2020) - Zhan, Zi-Ying; Wu, Mei; Shang, Yue; Jiang, Min; Liu, Jian; Qiao, Chun-Ying; Ye, Huan; Lin, Yong-Ce; Piao, Mei-Hua; Sun, Rong-Hui; Zhang, Zhi-Hong; Jiao, Jing-Ya; et al.
Abstract : Taxifolin ameliorated steatohepatitis induced by long-term HFD feeding plus alcohol binge through modulation of SREBP1 and PPARγ, targeting pyroptotic inflammation related IL-1β release and Caspase-1 activation. Abstract : Excessive alcohol drinking and a high-fat diet (HFD) promote steatohepatitis in the comorbidity of NAFLD and AFLD. Taxifolin (TAX) is a rich dihydroxyflavone compound found in onions, milk thistle and Douglas fir. We aimed to explore the intervention mechanism of TAX on chronic steatohepatitis induced by HFD feeding plus acute ethanol binge. We established an in vivo model by HFD feeding plus a single dose of ethanol binge, and established an in vitro model by oleic acid or palmitic acid on HepG2 cells to induce lipid accumulation. TAX regulated lipid synthesis by inhibiting the expression of SREBP1 and upregulating the PPARγ level. In addition, TAX inhibited the expression of P2X7R, IL-1β, and caspase-1. Moreover, TAX reduced the expression of caspase-1 activation; thereby inhibiting the recruitment of macrophages and neutrophils. TAX also improved the inflammatory response caused by caspase-1 activation in steatotic hepatocytes. TAX exhibited an inhibitory effect on lipid accumulation and caspase-1-related pyroptosis. Collectively, TAX has therapeutic potential as an intervention of steatohepatitis induced by alcohol combined with HFD and for preventing non-alcoholic fatty liver degeneration targeting caspase-1-dependent pyroptosis.